Enhancement and Optimization of Solar Dryer: A Review - Gaur, Aditya (Asian Review of Mechanical Engineering, 2021)
Infinite accessibility of solar energy and continuously reducing reserves of fossil fuel has led the humankind to use solar energy in efficient way for various requirements. One of the important requirements is drying, i.e. drying of various edible products, crops, etc. Research has been done on various ways to improve dryer efficiency, which includes depleting drying time, improving product quality coming out of dryer, minimizing energy loss, etc. This paper reviews the previous work done on optimization and enhancement of solar dryer. Techniques for optimizing solar dryer such as Artificial Neural Network, Genetic Algorithm, Response Surface Methodology, etc. have been studied whereas use of energy storage medium like Phase Change Material and other factors like geometrical parameter, solar dryer with thermal storage for enhancement of solar dryer has been reviewed.